Optimizing for Happiness and Productivity: Modeling Opportune Moments for Transitions and Breaks at Work - Kaur, Harmanpreet; Williams, Alex C.; McDuff, Daniel; Czerwinski, Mary; Teevan, Jaime; Iqbal, Shamsi (ACM Conference on Human Factors in Computing Systems (CHI), 2020)
Information workers perform jobs that demand constant multitasking, leading to context switches, productivity loss, stress, and unhappiness. Systems that can mediate task transitions and breaks have the potential to keep people both productive and happy. We explore a crucial initial step for this goal: finding opportune moments to recommend transitions and breaks without disrupting people during focused states. Using affect, workstation activity, and task data from a three-week field study (N = 25), we build models to predict whether a person should continue their task, transition to a new task, or take a break. The R2 values of our models are as high as 0.7, with only 15% error cases. We ask users to evaluate the timing of recommendations provided by a recommender that relies on these models. Our study shows that users find our transition and break recommendations to be well-timed, rating them as 86% and 77% accurate, respectively. We conclude with a discussion of the implications for intelligent systems that seek to guide task transitions and manage interruptions at work.